2019
DOI: 10.1021/acs.jctc.9b00801
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-Up Simulations of Diffusion in Microporous Materials

Abstract: We introduce and demonstrate the coarse-graining of static and dynamical properties of host-guest systems constituted by methane in two different microporous materials. The reference systems are mapped to occupancy-based pore-scale lattice models.Each coarse-grained model is equipped with an appropriate coarse-grained potential and a local dynamical operator, which represents the probability of inter-pore molecular jumps between different cages. Both the coarse-grained thermodynamics and dynamics are defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Since temporal channel fluctuations increase transport coefficients, and since inter-particle interactions, or crowding effects, generally decrease diffusion, it is natural to ask if one can predict which effect dominates. Even though recent numerical work showed that diffusion enhancement could be obtained with increased particle density in microporous matrices (Obliger et al 2019), sometimes even exhibiting a maximum (Pireddu et al 2019) at a certain density, it was also noticed that the effect can depend strongly on the precise details of the system understudy (Obliger et al 2023). These results thus call for a general theoretical investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since temporal channel fluctuations increase transport coefficients, and since inter-particle interactions, or crowding effects, generally decrease diffusion, it is natural to ask if one can predict which effect dominates. Even though recent numerical work showed that diffusion enhancement could be obtained with increased particle density in microporous matrices (Obliger et al 2019), sometimes even exhibiting a maximum (Pireddu et al 2019) at a certain density, it was also noticed that the effect can depend strongly on the precise details of the system understudy (Obliger et al 2023). These results thus call for a general theoretical investigation.…”
Section: Introductionmentioning
confidence: 99%
“…2019), sometimes even exhibiting a maximum (Pireddu et al. 2019) at a certain density, it was also noticed that the effect can depend strongly on the precise details of the system understudy (Obliger et al. 2023).…”
Section: Introductionmentioning
confidence: 99%